REINTERPRETASI TRADISI HAROA DI BUTON MELALUI METODE DOUBLE MOVEMENT FAZLUR RAHMAN - Rahmaniar, Wa Ode (Ahsan: Jurnal Dakwah dan Komunikasi, 2025)
This study reinterprets the Haroa tradition a Buton ritual of gratitude rich in spiritual and social values using Fazlur Rahman's double movement hermeneutic method to address questions regarding its theological legitimacy. Employing a qualitative library research approach, the study analyzes Haroa culture and Rahman's methodology. The analysis through Rahman's First Movement reveals that Haroa emerged from an accommodative Islamization process, integrating Islamic principles into local culture. The core normative values found gratitude, social solidarity, and moral education are consistent with the ethical values of the Qur'an. The Second Movement confirms the enduring relevance of these moral values in the modern context. Haroa functions as a crucial space for collective ethical education and dialog amidst contemporary social challenges like individualism and weakening solidarity. In conclusion, the Haroa tradition is recognized as urf shalih (a good tradition) in line with Sharia principles. It possesses a strong, relevant theological value foundation, acting as an effective medium for the contextual internalization of Qur’anic morals within the Buton community.